Rare case of littoral cell angioma recognised on CT simulation for adjuvant radiation treatment for early stage breast cancer. Issue 2 (7th February 2022) - Yaney, Alexander; Jones, Daniel; Perry, Kyle A; Jhawar, Sachin R
Abstract : A 63-year-old woman with pathological anatomic/prognostic stage IA ER+/PR+/HER2- multifocal invasive mammary carcinoma with mixed ductal and lobular features of the left breast underwent lumpectomy with sentinel lymph node biopsy. During evaluation of the CT simulation for adjuvant radiation (RT) treatment planning, a liver lesion and splenomegaly were noted. A subsequent MRI abdomen revealed a large, indeterminate splenic lesion with a wide differential and a benign liver cyst. The patient ultimately underwent splenectomy, with pathology consistent with littoral cell angioma, a rare entity associated with several malignancies. At last follow-up, 7 months after completion of RT, she remained cancer free while on anastrazole and was doing well clinically.